The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1017/s0022215106005226
|View full text |Cite
|
Sign up to set email alerts
|

Hearing threshold assessment post grommet insertion. Is it reliable?

Abstract: We aimed to investigate whether auditory brainstem response (ABR), assessed immediately after grommet insertion, was an accurate measure of hearing threshold. Ten children were recruited (20 ears). Patients underwent transient evoked otoacoustic emission (TEOAE) and ABR tests before and after grommet insertion under general anaesthetic. A third assessment was conducted at a six-week review, without anaesthetic or sedation. The hearing threshold in dB and the presence of TEOAE were recorded by senior audiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Early studies reported improved hearing immediately after tube placement by ABR testing and justified the use of ABR testing in the OR [10,11]. Clinical studies in recent years have revealed significant discrepancies between ABR results obtained in the OR and those obtained in the follow-up period, raising a concern regarding the validity of ABR outcomes obtained in the OR [7][8][9]. It is argued that OR-ABR results may not reflect patients' real hearing thresholds, therefore, follow-up audiological evaluations should be performed when OR-ABR indicates a hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies reported improved hearing immediately after tube placement by ABR testing and justified the use of ABR testing in the OR [10,11]. Clinical studies in recent years have revealed significant discrepancies between ABR results obtained in the OR and those obtained in the follow-up period, raising a concern regarding the validity of ABR outcomes obtained in the OR [7][8][9]. It is argued that OR-ABR results may not reflect patients' real hearing thresholds, therefore, follow-up audiological evaluations should be performed when OR-ABR indicates a hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that ABR thresholds following aspiration of middle ear fluid should be interpreted with caution. In 2007, Griffiths et al investigated whether the ABR, assessed immediately after tube insertion, was an accurate measure of hearing threshold [8]. Among the 10 subjects (20 ears) studied, threshold shifts of 15 dB or greater were observed in 7 ears after tube insertion.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended that follow-up testing should not be done until two to three weeks after fluid removal to better ensure resolution of middle ear disease. 6 Griffiths et al 7 prospectively performed transient evoked otoacoustic emissions and ABRs in 10 children immediately before, immediately after, and six weeks following tube insertion. Comparing the six-week review ABR with the postoperative ABR, 13 ears had decreased thresholds, by as much as 20 dB.…”
Section: Discussionmentioning
confidence: 99%
“…Griffiths et al7 prospectively performed transient evoked otoacoustic emissions and ABRs in 10 children immediately before, immediately after, and six weeks following tube insertion. Comparing the six‐week review ABR with the postoperative ABR, 13 ears had decreased thresholds, by as much as 20 dB.…”
Section: Discussionmentioning
confidence: 99%